Yevtushenko : selected poems - Yevtushenko, Yevgeny Aleksandrovich, 1933-2017 (Penguin classics., 2008)
'So there stood youth and there childhood together, Trying to look into each other's eyes'This volume contains a selection of early works by Yevgeny Alexandrovich Yevtushenko (b. 1933), who blazed a trail for a generation of Soviet poets with a confident poetic voice that moves effortlessly between social and personal themes. 'Zima Junction' vividly describes his idyllic childhood in Siberia and his impressions of home after a long absence in Moscow. Private moments are captured in 'Waking', on the joys of discovering the unexpected in a lover, and 'Birthday', on a mothers concern for her son, while 'Encounter' depicts an unexpected meeting with Hemingway in Copenhagen. `The Companion' and 'Party Card' show war from a child's eye, whether playing while oblivious to German bombs falling nearby or discovering a fatally wounded soldier in the forest, while Yevtushenko's famous poem, 'Babiy Yar, is an angry expose of the Nazi massacre of the Jews of Kiev. The imaginative translations by Robin Milner-Gulland and Peter Levi bring the poems of Yevtushenko to life for readers in English, while Robin Milner-Gulland's introduction discusses Yevtushenko's literart career and the originality of his poems.